Increasing Student Cooperation Through A Project-Based Learning Model with the Theme of Ecosystems - Hermawati, Risca; Chen, Diki (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research is based on the fact that there are still many students class VA elementary school less able to work well together and the creation of learning conditions that are less comfortable for some students. Students who are still not able to work well together, teachers put forward the cognitive aspects of students only, without improving the affective and psychomotor aspects. Methodology: This study is a classroom action research consisting of three cycles, where the data taken in the form of observation data through student collaboration observation sheet and teacher observation sheet conducted in each learning process using a project-based learning model. Main Findings: The results of this study indicate that the implementation of project-based learning model can improve the cooperation of VA elementary school students. Based on students' observation sheets, student cooperation showed an increase, as evident from the cycle I of student cooperation 59.4%, increased in cycle II to 72.8%, and increased again in cycle III 78.8% Novelty/Originality of this study: In this case it can be concluded that the project-based learning model can improve student cooperation on the theme of ecosystem in VA elementary school class.